The place of memory. The place of the other. Viewpoint as an articulating axis of experience. A didactic proposal - López F. Cao, Marián (Pulso. Revista de educación, 2002)
This text aims to present a didactic approach in the field of visual arts that uses critical pedagogy to provide tools for reading and production. The objective is to prompt students to put themselves in others' shoes, to acknowledge themselves beyond their own image, to be taken aback by their own assumptions, to comprehend the image, and ultimately, to introspect and reject social stereotypes that classify, discriminate, and isolate.